Decoding oral leukoplakia: microbiome dysbiosis and inflammatory dynamics unveiled in a rat model - Sang, Zhiqin; Zhang, Yufeng; Kao, Enoch; Zhu, Tingting; Yang, Jiazhen; Xu, Zhenjiang Zech; Huang, Shi; Teng, Fei; Wang, Wanchun (Frontiers in Microbiology, 2025)
IntroductionOral leukoplakia (OLK) is an oral precancerous lesion associated with oral microbiome dysbiosis and systemic inflammation. However, the longitudinal changes of the microbiome and its causal relationship with inflammation remain unclear, and traditional sequencing struggles to detect low-biomass samples.MethodsA 4-nitroquinoline-1-oxide (4-NQO)-induced rat OLK model was used. The oral microbiome was analyzed via 2bRAD-M sequencing; serum levels of tumor necrosis factor-α (TNF-α) and interleukin-6 (IL-6) were measured. Additionally, functional pathway analysis of the microbiome and its correlation with inflammation were conducted.ResultsIn OLK, we observed significant shifts in the oral microbial diversity, marked by elevated abundances of Streptococcus, Glaesserella, and Pseudomonas aeruginosa. Moreover, shifts in the microbiota precede the manifestation of clinical symptoms of OLK. Functional pathway analysis highlighted enrichment in metabolism, quorum sensing, and cancer-associated microRNA pathways. Serum levels of inflammatory markers (TNF-α and IL-6) were significantly elevated in OLK and significantly correlated with specific bacterial taxa.DiscussionThis study demonstrates the utility of 2bRAD-M sequencing in overcoming traditional metagenomic limitations, offering a high-resolution view of microbiome dynamics in low-biomass environments such as the oral mucosa. These findings establish the oral microbiota as candidate early biomarkers for OLK screening and prevention, opening avenues for precision diagnostics and targeted therapies to mitigate cancer risk associated with OLK.